Theories of Etiopathogenesis of Breast Implant–Associated Anaplastic Large Cell Lymphoma. (March 2019) - Rastogi, Pratik; Riordan, Edward; Moon, David; Deva, Anand K.
Abstract : Summary: Breast implant–associated anaplastic large cell lymphoma is a malignancy of T lymphocytes that is associated with the use of textured breast implants in both esthetic and reconstructive surgeries. Patients typically present with a delayed seroma 8–10 years following implantation or—less commonly—with a capsular mass or systemic disease. Current theories on disease pathogenesis focus on the interplay among textured implants, Gram-negative bacteria, host genetics, and time. The possible roles of silicone leachables and particles have been less well substantiated. This review aims to synthesize the existing scientific evidence regarding breast implant–associated anaplastic large cell lymphoma etiopathogenesis.